Raw starch-degrading enzyme from newly isolated strains of endophytic fungi - Marlida, Yetti; Saari, Nazamid; Hassan, Zaiton; Radu, Son (Springer, 2000)
Four newly isolated strains of endophytic fungi namely Gibberella pulicaris, Acremonium sp., "Synnematous" sp. and Nodilusporium sp. were compared for their degradative activity on raw and gelatinized starches, substrate specificity and optimum pH. Results showed that the raw starch-degrading enzyme from Acremonium sp. had a broad activity towards both small and large granule size of raw starches while the enzyme from other strains showed high activity toward starches of smaller granule size. Analysis of the end product by TLC showed that enzyme from Gibberella pulicaris, Acremonium and Nodilusporium sp. hydrolysed raw sago starch to produce solely glucose but the enzyme of "Synnematous" sp. produced glucose and maltose.